2003
DOI: 10.1038/sj.bmt.1703836
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib mesylate (STI-571) given concurrently with nonmyeloablative stem cell transplantation did not compromise engraftment and resulted in cytogenetic remission in a patient with chronic myeloid leukemia in blast crisis

Abstract: Summary:The main obstacles to successful hematopoietic stem cell transplantation for patients with chronic myeloid leukemia (CML) in blast crisis (BC) are increased posttransplant relapse and high treatment-related mortality. We report a patient with CML in BC who was treated initially with imatinib mesylate and was then concurrently treated with a nonmyeloablative stem cell transplant. Successful engraftment of donor cells followed by complete cytogenetic remission was achieved in the absence of severe therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Previous reports had shown the results of allogeneic transplantation to be not negatively influenced by prior IM. Three case reports describe the successful treatment of advanced phase CML with IM before and after reduced-intensity conditioning and allogeneic HCT (19)(20)(21). Two larger studies summarize patients who had received IM for treatment of relapsed Ph+ acute lymphoblastic leukaemia or advanced CML and then received either allogeneic HCT or donor lymphocyte infusions (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports had shown the results of allogeneic transplantation to be not negatively influenced by prior IM. Three case reports describe the successful treatment of advanced phase CML with IM before and after reduced-intensity conditioning and allogeneic HCT (19)(20)(21). Two larger studies summarize patients who had received IM for treatment of relapsed Ph+ acute lymphoblastic leukaemia or advanced CML and then received either allogeneic HCT or donor lymphocyte infusions (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil counts of ‡500/lL were reached after a median of 15 d (range [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Platelet counts of ‡50 000/lL for 7 d were reached after a median of 18 d (range 0-83).…”
Section: Engraftmentmentioning
confidence: 99%
“…31,32 Preliminary data from a patient treated with a nonmyeloablative stem cell transplant and receiving imatinib concomitantly is also consistent with this notion. 33 Liver toxicity is a common and potentially fatal complication after myeloablative conditioning therapy. Previous studies showed that transplants recipients with pre-existing liver injury had an increased risk of liver complications and death.…”
Section: Discussionmentioning
confidence: 99%
“…Both BMT and PBSC transplantation have provided reasonable results in the patients, even in those who were treated with IFN or imatinib before transplantation. 20,21 Furthermore, minimal residual clones of Ph1 were eradicated by post-HSCT donor lymphocyte infusion. 22,23 Use of UCBT in patients with CML was first reported by Rubinstein et al 3 in the context of haematopoietic malignancies.…”
Section: Introductionmentioning
confidence: 99%